Education and Wage Differentials in the Philippines - Luo, Xubei; Terada, Takanobu (2012)
In the Philippines, an important part of income inequality is associated with the wage difference between the less educated and the better educated. The majority of the least educated are employed in low-paid services jobs and the agricultural sector. Tertiary education is to a large extent a prerequisite for high-paid occupations. Using the Labor Force Survey 2003-2007, this paper examines disparities in human capital endowment, returns to education, and the role of education in wage differentials in the Philippines. The empirical results show that returns to education monotonically increase - workers with elementary education, secondary education, and tertiary education earn 10 percent, 40 percent, and 100 percent more than those with no education. The results also show that education is the single most important factor that contributes to wage differentials. At the national level, education accounts for about 30 percent of the difference in wages. It accounts for a higher percentage of the difference for female workers (37 percent) than male workers (24 percent). There are also differences across regions and sectors. As an economy develops, the demand for skills increases. In the Philippines, efforts to improve education to increase the supply of highly educated people are important not only for long-term growth, but also for helping to translate growth into more equal opportunities for the children of the current generation.